Books, type and Cyprus: A digital archive on the web - Panayides, Omiros (My University, 2023)
Graphic design, as a professional field, is arguably a young discipline. The commercial trade of the 18th and 19th centuries, the labeling of conflicts and wars, political agendas and propaganda formed this new visual language into projects that were archived and exhibited, stories that were printed and disseminated, courses that were taught and studied. Graphic design history is based on popularity, personal preference/taste, predefined agendas and the social status of the people that have written and rewritten about it. A selection of figures and collective movements that have impacted the evolution and history of the modern design world. Graphic design history, for the most part, is made of movements that stretch only as far as the Western eye has been trained to see. But what about the design happening at the peripheries and in the margins? I would argue that it is our shared visual experiences, and not global trends, that mean the most for communities at the fringes of design history. In an interview in 2008, the Dutch design group Experimental Jetset said: ‘True, graphic design is being marginalized, but let’s not forget that margins are in fact graphic spaces; the margins are ours.’ Cyprus is such a case of a marginalized country with its own messy history. Α bite-size xenomaniac postcolonial country, wearing proudly its European cape, over its middle eastern core. There has been little to no documentation of its graphic design (previously commercial art) footprints and a handful of references in the academic world. This research project titled Books, Type and Cyprus is a study on typography and images found οn covers of literature and poetry books in Cyprus. This archive is an attempt to build an appreciation towards the local graphic design scene, writing its own design narrative, oriented for designers, book enthusiasts, writers, and the humanistic field.
Keywords: Typography; Images; Literature; Poetry; Books; Cyprus